Intention and Performance: A Primer of Cybernetics of Planning - Greniewski, Henryk (Management Science, 1965)
It is claimed that the object of a plan is always a relatively isolated prospective system: the goal is a certain state of the output; the means are the states of the controlled inputs; and the circumstances under which the goal is to be attained are the states of the uncontrolled inputs. The relationships as between the goal, the means, and the circumstances are analyzed; planning is given a game theoretical interpretation; the implementation of a plan is a two-person game, the planner, and the circumstances being the two players. The concepts of a revision of the plan, the logical structure of the plan, and the various types of the models of planning are also discussed.